2020
DOI: 10.6008/cbpc2179-6858.2020.002.0014
|View full text |Cite
|
Sign up to set email alerts
|

2.4-Dichlorophenoxyacetic acid and sucrose in rhizogenesis maintenance and induction in cuttings of cagaita and mangabeira from cerrado

Abstract: The Cerrado has a vast diversity of fruit plant species. Among them, the cagaita and mangabeira trees stand out because of their fruits nutritional potential. They propagate through seeds, a method that generates genetically distinct plants. Thus, it would be of interest to propagate these plants through vegetative propagation techniques aiming to select superior and identical genotypes from the mother plant. Therefore, the objective was to establish a methodology for maintenance, survival, and rooting inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…Por outro lado, Ferreira e Ferrari (2010) obtiveram enraizamentos médios próximos dos 90% em estacas de atemoieira (Annona cherimola Mill. x A. squamosa L.) tratadas tanto com AIB quanto 2,4-D nas concentrações de 0, 500, 1000, 2000, 3000, 4000 e 5000 mg L -1 durante 5 s. Vieira et al (2020) avaliaram o enraizamento de estacas de mangabeira (Hancornia speciosa var. pubescens) tratadas com soluções de sacarose (0, 10, 20, 30 e 40%) acrescidas de 3 mg L -1 de 2,4-D e constataram que o uso do 2,4-D auxiliou na formação das raízes adventícias, embora tenham sugerido o uso de concentrações mais diluídas deste regulador de crescimento devida a alta taxa de mortalidade de estacas obtida.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Por outro lado, Ferreira e Ferrari (2010) obtiveram enraizamentos médios próximos dos 90% em estacas de atemoieira (Annona cherimola Mill. x A. squamosa L.) tratadas tanto com AIB quanto 2,4-D nas concentrações de 0, 500, 1000, 2000, 3000, 4000 e 5000 mg L -1 durante 5 s. Vieira et al (2020) avaliaram o enraizamento de estacas de mangabeira (Hancornia speciosa var. pubescens) tratadas com soluções de sacarose (0, 10, 20, 30 e 40%) acrescidas de 3 mg L -1 de 2,4-D e constataram que o uso do 2,4-D auxiliou na formação das raízes adventícias, embora tenham sugerido o uso de concentrações mais diluídas deste regulador de crescimento devida a alta taxa de mortalidade de estacas obtida.…”
Section: Resultsunclassified
“…É importante destacar os resultados inferiores promovidos pelo 2,4-D nas características número de raízes e massas fresca e seca de raízes (Tabela 1), pois reforça a teoria de que esta substância pode ter realmente provocado efeito herbicida nas estacas de figueira. Vieira et al (2020) também relataram o possível efeito herbicida do 2,4-D em estacas de mangabeira quando foram tratadas com soluções de sacarose (0, 10, 20, 30 e 40%) acrescidas de 3 mg L -1 deste regulador de crescimento. Tofanelli et al (2014) estudaram o efeito da aplicação do 2,4-D e AIB em estacas de porta-enxertos de videira (Vitis ssp) nas concentrações de 0, 1000, 2000 e 3000 mg L -1 e obtiveram queda no número de raízes por estaca à medida que se aumentava as concentrações de 2,4-D. Já Uyoh et al (2016) destacaram que as concentrações de AIB e 2,4-D (10.000, 30.000 e 50.000 mg L -1 ) quando aplicadas em estacas de inhame da Índia (Dioscorea alata L.) não promoveram os mesmos resultados em relação às também testadas soluções naturais promotoras do enraizamento a base de água de coco ou cinzas de folha de neem nas mesmas concentrações provavelmente porque, conforme os mesmos autores, as concentrações de ambos reguladores de crescimento não favorecerem a formação de raízes no mesmo nível dos enraizadores naturais.…”
Section: Resultsunclassified
“…Regarding staking, the study by Soares et al (2020) revealed total mortality of the cuttings, but no anatomical impediments were found for the rooting of the cuttings. Vieira et al (2020) observed a 100% survival of the cuttings, but only with the emission of root primordia. No scientific articles on the propagation of mangabeira by air layering were found in the review.…”
Section: Production Of Seedlingsmentioning
confidence: 93%
“…• Both herbaceous and woody stem cuttings presented total mortality and lack of rooting, independently of the high concentrations of IAB (indol butyric acid) and the origin of the cuttings. (Vieira et al, 2020;Soares et al, 2020)…”
Section: Cuttingsmentioning
confidence: 99%